Comparison Between PET-CT–Guided Neck Dissection and Elective Neck Dissection in cT1-2N0 Tongue Squamous Cell Carcinoma - Zhu, Fengjie; Sun, Shuhan; Ba, Kai (Frontiers in Oncology, 2020)
Objective: Neck management in cT1-2N0 tongue squamous cell carcinoma (SCC) remains controversial. Our goal was to compare the survival difference between PET-CT-guided neck dissection and elective neck dissection (END) for the treatment of cT1-2 tongue SCC. Methods: Patients with surgically treated cT1-2N0 tongue SCC were retrospectively enrolled. These patients were divided into two groups. Group A: the decision of whether to perform neck dissection was mainly based on the results of preoperative PET-CT examinations. Group B: patients received END treatment without preoperative PET-CT examinations. The study endpoints were regional control (RC) and disease-specific survival (DSS). The Kaplan-Meier method was used to calculate the survival rates. Results: Group A consisted of 66 patients, where 16 patients underwent neck dissection owing to positive PET-CT results, and group B consisted of 169 patients. The 5-year RC rates in group A and group B were 86% and 87%, respectively, and the difference was not significant (p=0.731). The 5-year DSS rates in group A and group B were 93% and 90%, respectively, and the difference was not significant (p=0.583). Conclusions: Neck dissection could be safely avoided when the PET-CT scan reveals no neck lymph node involvement.